Predictive and perceptual phonemic processing in articulatory motor areas: A prediction potential & mismatch negativity study. (October 2022) - Grisoni, Luigi; Pulvermüller, Friedemann
Abstract: The recent finding of predictive brain signals preceding anticipated perceptual and linguistic stimuli opens new questions for experimental research. Here, we address the possible brain basis of phonological predictions regarding the features of specific speech sounds and their relationship to phonological priming. To this end, we recorded EEG correlates of both pre- and post-stimulus brain responses in a phonological priming study. Redundant spoken sounds induced stimulus expectations, which manifested as a slow-wave anticipatory activity (the Prediction Potential, PP), whereas articulatory-congruent (e.g., /bƏ/in the context of expected/pƏ/) pairs elicited weaker post-stimulus MMN-like responses as compared to the articulatory-incongruent (e.g., /bƏ/in the context of expected/dƏ/) pairs, a pattern reminiscent of perceptual priming mediated by articulatory-motor areas. Source analysis reveal clusters of activation in lateral prefrontal, temporal and ventral motor areas, thus providing the proof of the relevance of multimodal representation units subserving predictive and perceptual phonemic processing.